Evaluasi Profil Sensori Produk Kopi Instan Starbucks VIA Ready Brew Unflavored Menggunakan Metode CATA (Check-All-That-Apply) - Ardiansyah Saputra, Reza; Kartika Pratiwi, I Desak Putu; Yusasrini, Ni Luh Ari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPA, 2023)
Coffee has a distinctive aroma and taste, and it is usually served in the form of drinks. This study aimed to determine the sensory profile of Starbucks instant coffee VIA ready brew unflavored based on consumer acceptance by CATA (Check All That Apply) method and to identify the consumer preferences maps. There were three variant of Starbucks instant coffee VIA ready brew unflavored as follows: VIA colombia, VIA pike place and VIA italian roast that tested on 34 panelists. Each panelist gave response of CATA acceptance with the attribute that already issued. The data analyzed by XLSTAT 2021 software with sensory data analysis and preference mapping (PREFMAP) features. Sensory profile were interpreted through three analyzes such as Cochran’s Q test, Correspondence Analysis and Principal Coordinate Analysis (PCoA). The ideal instant coffee based on biplot map were the attributes of a bitter taste, smoky aroma, viscosity mouthfeel and bitter aftertaste. The sensory profile evaluation results from the 3 variants of VIA ready brew unflavored were as follows: VIA colombia has the attributes of sour taste, fruity aroma, nutty aroma, watery mouthfeel and sour aftertaste, VIA pike place has the attributes of bitter taste, nutty aroma, viscosity mouthfeel and bitter aftertaste, VIA italian roast has the attributes of bitter taste, smoky aroma, viscosity mouthfeel and bitter aftertaste. The result of preference mapping showed that VIA italian roast had the ideal sensory profile with the highest level of preference.